2022
DOI: 10.3390/jcm11051193
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis Reduced Venous Thromboembolism in Sickle Cell Patients with Central Venous Access Devices: A Retrospective Cohort Study

Abstract: Sickle cell disease (SCD) induces a chronic prothrombotic state. Central venous access devices (CVADs) are commonly used for chronic transfusions and iron chelation in this population. CVADs are an additional venous thromboembolism (VTE) risk factor. The role of thromboprophylaxis in this setting is uncertain. The objectives are: (1) to determine whether thromboprophylaxis reduces VTE risk in SCD patients with CVAD and (2) to explore characteristics associated with VTE risk. We identified adults with SCD and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, it has been recently shown in France that ACS was associated with pulmonary thrombosis in 3%–17% of cases. 19 Other causes of thrombosis in SCD are mainly represented by venous catheters due to poor venous access, 20 often during a hospitalisation for VOC. The lack of association between HVOC and stroke is probably due to the chronic blood exchange transfusions in patients with cerebral vasculopathy and possibly a different pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been recently shown in France that ACS was associated with pulmonary thrombosis in 3%–17% of cases. 19 Other causes of thrombosis in SCD are mainly represented by venous catheters due to poor venous access, 20 often during a hospitalisation for VOC. The lack of association between HVOC and stroke is probably due to the chronic blood exchange transfusions in patients with cerebral vasculopathy and possibly a different pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a retrospective chart review of 52 patients with SCD and CVC, patients who received pharmacologic TP for the CVC were less likely to have a CRT. 63 On multivariate analysis, after adjustment for sex, age, additional VTE risk factors, hydroxyurea, thromboprophylaxis, BMI and CVAD subtype, the relative rate reduction of VTE with thromboprophylaxis was 14.9 (2.0-108.7) (p = 0.01). In this model, hydroxyurea was also strongly associated with a reduced rate of VTE events (RR = 47.1 [8.0-276.0] [p < 0.001]).…”
Section: Presence Of Cvcmentioning
confidence: 98%
“…In ambulatory cancer patients, who are similarly at high risk for VTE, those with a VTE risk of 10% or greater at 6 months are considered for thromboprophylaxis 10. There remains strong potential for clinical benefit with thromboprophylaxis in SCD with CVC, as a recent retrospective multicentre observational study found lack of thromboprophylaxis compared with thromboprophylaxis with any antithrombotic agent, was associated with a rate ratio for VTE of 4.0 (95% CI 1.2 to 12.6) 11. However, there is also potential for harm, as SCD also has a predisposition to bleeding, including haemorrhagic stroke, vitreous haemorrhage and haematuria.…”
Section: Introductionmentioning
confidence: 99%
“… 10 There remains strong potential for clinical benefit with thromboprophylaxis in SCD with CVC, as a recent retrospective multicentre observational study found lack of thromboprophylaxis compared with thromboprophylaxis with any antithrombotic agent, was associated with a rate ratio for VTE of 4.0 (95% CI 1.2 to 12.6). 11 However, there is also potential for harm, as SCD also has a predisposition to bleeding, including haemorrhagic stroke, vitreous haemorrhage and haematuria. In a population-based study, individuals with SCD had a cumulative incidence of bleeding requiring emergency department or hospitalisations of 21% (95% CI 19.8% to 22.3%) by age 40.…”
Section: Introductionmentioning
confidence: 99%